just as powers of products add (6^2 * 6^3 = 6^5) and subtract (6^8 / 6^3 = 6^5)
log of a product is the sum of the logs, and log of a quotient is difference of logs. That's because of the definition of log:
log6N is the power of 6 needed to get N. Even though it looks weird, a log is just an exponent!
So, log x(x+5)/x^6
= logx + log(x+5) - log x^6
Now, log x^6 = log x*x*x*x*x*x = logx + logx + logx + logx + logx = 6logx
and now qwe end up with
logx + log(x+5) - 6logx
= log(x+5) - 5logx
That could also have been achieved by noticing that
x(x+5)/x^6 = (x+5)/x^5
notice how the power subtracted when factoring out the x?
Expand using logarithm properties: log6 x(x+5)/x^6
I am so confused about this problem. Could anyone explain this to me?
1 answer